COGNITIVE LINGUISTICS AND THE CONCEPTUALIZATION OF TIME - Nabiulina Zarina Nailevna (Modern American Journals, 2025)
This article explores the role of cognitive linguistics in understanding how humans conceptualize time. Cognitive linguistics emphasizes the relationship between language, thought, and human experience, and it provides powerful frameworks for analyzing how abstract concepts such as time are structured in the mind. By focusing on metaphors, mental imagery, and cultural models, the study highlights the ways in which temporal concepts are understood through spatial and bodily experiences. The article examines how languages encode time through linear, cyclical, and spatial metaphors, as well as how cultural and linguistic contexts shape the perception of temporal flow. The findings suggest that time is not a universal, objective construct but rather a culturally mediated and cognitively grounded phenomenon. The article contributes to a deeper understanding of linguistic relativity, cross-cultural differences, and the pedagogical implications of teaching temporal expressions in foreign language classrooms.